2021
DOI: 10.1016/j.omtn.2020.10.011
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-Binding Protein CELF2 Inhibits Ovarian Cancer Progression by Stabilizing FAM198B

Abstract: An increasing number of studies have clarified the functional roles of RNA-binding proteins (RBPs) in driving post-transcriptional mechanisms of cancer progression. In this study, we integrated data from the RBP database and Gene Expression Omnibus (GEO) data with RNA sequencing (RNA-seq) data from 10 ovarian cancer tissues and 8 normal ovarian tissues and identified an RBP, CUGBP- and ETR-3-like family 2 (CELF2). We found that CELF2 expression was downregulated in ovarian cancer and positively correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 48 publications
0
47
0
Order By: Relevance
“…Multiple studies have confirmed that CELF2 exerts tumour suppressive effects in most tumours, which is significantly increased in developing thymocytes and activated T cells, but its comprehensive understanding within the TME remains unknown 16–26 . Therefore, it is necessary to investigate the relationships between CELF2 expression and TIIC infiltration in the TME.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple studies have confirmed that CELF2 exerts tumour suppressive effects in most tumours, which is significantly increased in developing thymocytes and activated T cells, but its comprehensive understanding within the TME remains unknown 16–26 . Therefore, it is necessary to investigate the relationships between CELF2 expression and TIIC infiltration in the TME.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that CELF2 could regulate multiple steps of RNA processing, such as pre‐mRNA splicing, RNA editing, polyadenylation, mRNA stability and translation 14,15 . Over the past decade, substantial studies have confirmed that CELF2 played a tumour suppressor role in breast cancer, lung cancer, hepatocellular carcinoma, gastric cancer, ovarian cancer, glioma and acute myeloid leukaemia, suggesting that it can be used as a candidate biomarker to predict cancer prognosis 16–23 . Additionally, CELF2 expression was significantly elevated in developing thymocytes and activated T cells and promoted T‐cell receptor expression and signalling through alternative splicing 24–26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, RPS3 stabilized SIRT1 mRNA by binding to AUUUA motifs on the 3’UTR of SIRT1 mRNA. In ovarian cancer, CELF2 could stabilize FAM198B mRNA by binding to AU/U-rich elements (AREs) in the 3’UTR ( 25 ). Moreover, ZFP36L1 bound to the HIF1A 3’UTR and mediated HIF1A mRNA degradation in bladder and breast cells ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…The above studies have fully con rmed that CELF2 may be a key gene regulating the occurrence and development of PC. Previous studies have demonstrated that CELF2 could play an important role in many kinds of tumors, including liver cancer [16], ovarian cancer [17], breast cancer [18], and gastric cancer [19]. Jakstaite et al found that overexpression of CELF2 can enhance the chemosensitivity of PC cells [20].…”
Section: Discussionmentioning
confidence: 99%